The effect of resistance band training on the forehand smash speed of youth male badminton singles players - Rahadhi, Danan Satria; Kusdinar, Yopi; Awwaludin, Patriana Nurmansyah; Mulyana , Mulyana (Physical Education and Sports: Studies and Research, 2025)
Background: Forehand smash shots kill opponents with explosive blows in a badminton game.  In hitting a forehand smash, there are several problems, one of which is the speed of the punch. Objectives: This study is designed to investigate and identify alternative exercises that can enhance the speed of smash shots. The findings of this study are expected to provide valuable insights for athletes and trainers, aiding in the development of effective training programs. Methods: The research method used in this study is an experimental method with a quantitative approach and a Two Group Pretest-Posttest Design research design. The population in this study were PB Pasundan Bandung badminton athletes, totaling 30 athletes, with a sample of 20 people using a purposive sampling technique. The instrument in this study used a smash shot speed test using the Velocity Speed Gun tool. The data was processed and analyzed using the normality test with Shapiro-Wilk and then analyzed using the independent t-test with SPSS 23. Results: The T-test value is with a Sig value. (2-tailed) of 0.00, based on the test results, the Sig value. (2-tailed) <0.05 so that H0 is rejected. So, resistance band training has a significant effect on increasing the speed of forehand smash shots. Conclusions: In conclusion, the consistent use of resistance bands in training sessions could be a game-changer in boosting the speed of forehand smash shots for badminton athletes. These results strongly advocate integrating resistance band training into early-stage badminton training programs. Future studies could further explore its long-term effects and application across different age groups, fostering hope for the continued evolution of training methods in badminton.